Superficial protection of concrete with epoxy resin impregnations: influence of the substrate roughness and moisture - Rodrigues, M. P. (2014)
One of the possible strategies to protect concrete from aggressive agents consists of applying impregnation products on its smface. This type of strategy is relatively often used in both new and existing structures. However, there are still several aspects conceming impregnation products whose understanding is still rather limited, inc1uding the influence of the concrete substrate on their performance. This paper presents an experimental study on the influence of the roughness and the moisture content of concrete substrates in the pelfOlmance of impregnation product~ used for superficial protection. For that purpose, two impregnations products based on epoxy resins were applied on concrete specimens with two different water/cement ratios (0.40 and 0.70). The concrete specimens were prepared according to different procedures, which created (i) three different smface roughnesses (no preparation, use of a 160 bar water jet and use of needle scalers) and (ii) three different moisture contents (3, 4.5 and 6 %). The perfOlmance of the protection systems was evaluated by means of the following tests suggested in EN 1504-2 standard: (i) product penetration depth; (ii) water absorption by immersion; (iii) abrasion resistance; (iv) impact resistance; and (v) bond strength. With the exception of the resistance to impact, the use of epoxy resins considerably improved the performance of the two types of concrete. Both surface roughness and moisture content proved to have a significant effect on the performance of the epoxy impregnations. However, such influence was different depending on the property at stake and the type of impregnation product.